AIRPORT SECURITY DETECTION C HECK WHAT ARE THE REAL LIMITS? (Perner's Contacts, 2017)
This article deals with one part of the ongoing project of the Air transport department of the University College of Business in Prague. This project aims to apply modern trends and knowledge in the process of detection checks at airports and thus to modify the screening sites on the basis of this knowledge. Partial goals of the project are behavioural detection and working environment. The text of the article itself deals with the boundary conditions of the project - about limits. These limits mainly concern the absence of the necessary legislative base in the EU. The aim of this article is to highlight important and rigorous marginal conditions in this area that do not allow innovative approaches to most scientific and other projects. That is why the project team of aimed at one of the outputs of the project also proposal for the direction of research activities in this sphere of civil aviation protection against unlawful acts. This article deals with this recommendation.